2019
DOI: 10.3390/ijerph16183464
|View full text |Cite
|
Sign up to set email alerts
|

Association between the Occurrence of Primary Hypothyroidism and the Exposure of the Population Near to Industrial Pollutants in São Paulo State, Brazil

Abstract: Background: Environmental agents interfere with thyroid function at multiple levels. This study was to investigate the association between pollutant concentrations and the primary hypothyroidism (PH) occurrence odds in residents living in the Capuava Petrochemical Complex (CPC) influence area. Methods: This area was evaluated with the combination of the AERMOD dispersion model with the Weather Research Forecast (WRF) meteorological model (2016). The concentration of atmospheric pollutants were analyzed in 2017… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 35 publications
3
14
0
1
Order By: Relevance
“…According to our results, the average concentrations of NO 2 , CO, PM10, SO 2 , and VOCs obtained from the simulated plumes in the cities studied are more signi cant in areas closer to the CPC (Table 4); this suggests that people living in those areas are more exposed to atmospheric pollutants than people who live far from the petrochemical industries and is consistent with many other studies (Kalabokas et al 2001;Ragothaman and Anderson 2017;Zaccarelli-Marino et al 2019).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…According to our results, the average concentrations of NO 2 , CO, PM10, SO 2 , and VOCs obtained from the simulated plumes in the cities studied are more signi cant in areas closer to the CPC (Table 4); this suggests that people living in those areas are more exposed to atmospheric pollutants than people who live far from the petrochemical industries and is consistent with many other studies (Kalabokas et al 2001;Ragothaman and Anderson 2017;Zaccarelli-Marino et al 2019).…”
Section: Discussionsupporting
confidence: 92%
“…Our previous studies (Zaccarelli -Marino 2012;Zaccarelli-Marino et al 2016 involved subjects living in a densely populated area of SP surrounding the Capuava Petrochemical Complex (CPC). We reported primary hypothyroidism (PH) (Zaccarelli- Marino et al 2016Marino et al , 2019 and an increase in the incidence of chronic autoimmune thyroiditis (CAT) over the years (Zaccarelli-Marino 2012) and showed evidence that iodine should not be considered the agent responsible for autoimmune thyropathies in Santo André (Marino et al 2009). Some of the results of the current study have been previously reported in the form of an abstract and poster presented at the ABC University Medical Congress (Zacarelli- Marino et al 2016aMarino et al , b, 2017aMarino et al , b, 2018a.…”
Section: Introductionmentioning
confidence: 99%
“…The high-level contamination of the area is primarily attributable to the presence of plants for the electricity production, a refinery, a steel plant and fuel oil power plant. At global level, the last three decades have been characterised by a significant increase of thyroid carcinoma, the most frequent endocrine malignancy, and, among the acknowledged risk factors including age, sex, radiation, a familiar history of thyroid cancer, 16 much evidence supports the likely etiological role of organic compounds (ie, PCBs, polybrominated diphenyl ethers, phthalates and bisphenols) and heavy metals (ie, Cd and Pb) that may act as thyroid disruptors through multiple mechanisms such as interference with thyroid hormone (TH) synthesis, TH metabolism and excretion, and TH action, 17 which, however, have not been completely elucidated. 18 19 In the early 2000s, a higher incidence and hospitalisation for thyroid cancer was observed in the population living in the NPCS of Milazzo when compared with the regional rate.…”
Section: Npcs Of Milazzo-valle Del Melamentioning
confidence: 99%
“…Meanwhile other studies have related human exposure to these compounds with an increase in cancer mortality, acute lower respiratory infections, asthma and cardiovascular diseases [6][7][8]. In addition, living in areas close to petrochemical complexes has also been related to increases in the occurrence of hypothyroidism [9] and pre-term births [10].…”
Section: Introductionmentioning
confidence: 99%